The Ability of Immunoglobulin Yolk Recognized the Antigen in the Tissue of Ascaridia galli - . Darmawi; U Balqis; M Hambal; R Tiuria; B P Priosoeryanto; E Handharyani (Media Peternakan, 2012)
Antigen-antibody reaction is an important tool for the analysis of localization of target molecules, including antigenic protein within worm tissues. The purpose of the present research was to demonstrate the ability of immunoglobulin yolk (IgY) anti-excretory/secretory recognized the antigen in the tissue of Ascaridia galli by mean of immunohistochemistry method. The excretory/secretory protein was procured from A. galli and concentrated by mean of vivaspin 30,000 MWCO. IgY was produced by egg yolks of immunized chickens with excretory/secretory, and purified using fast protein liquid chromatography (FPLC) method. A. galli adult worms were cut in transversal and longitudinal section of the center and anterior region. Slides were incubated with both primary IgY for overnight at 4 oC and secondary antibody rabbit anti-chicken IgY HRP-conjugate for one hour at room temperature. The slides were stained with 3-amino, 9-ethylcarbazole (AEC) chromogen, counterstained with Lillie Mayer Haematoxylin, and mounted in glyserin aqueous mount.  Antigen-antibody reaction was investigated under a microscope. The result showed that antigen was appeared in the tissues such as cuticle, epicuticle, buccal cavity, and eggs inside the uterine of A. galli. This research concluded that IgY stimulated by the excretory/secretory was able to recognized the antigen scattered in the tissues of A. galli so the IgY could be applied for immunodiagnostic.